Use of anti-citrullinated peptide (Anti–CCP) antibodies in distinguishing patients with systemic lupus erythematosus and rheumatoid arthritis (Medical Journal of Indonesia, 2004)
Diagnosis of Rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE) can be confused in their initial stages. The joints, especially the hands, are commonly affected in both disorders, many patients with SLE are initially misdiagnosed as having RA Given that the outcome for the two diseases is diverse, it would be helpful to have serological marker to distinguish between them at onset. Anti-citrullinated peptide antibodies (anti-CCP) have recently been described as highly specific for RA. The objective of this study is to confirm the specificity of anti-CCP antibodies and to determine whether they might distinguish patients with RA from those with SLE. This study is a cross sectional study on a group of patients with RA (n=27), SLE with arthritis (n=20), other autoimmune diseases (non-rheumatic diseases, n = 8), and healthy adults (n=20). Anti-CCP was determined by a commercial Elisa test and Rheumatoid factor (RF) was determined by the standard slide latex test. The sensitivity and specificity of anti-CCP for the diagnosis of RA was 63.0% and 97.9% respectively, comparing with RF for RA that was 40.7 % and 85.4 %. Only 1 healthy adult was anti-CCP+, no anti-CCP was detected from SLE and other autoimmune disease. The mean of titer anti CCP in normal healthy adult, other autoimmune diseases, SLE and RA was 1.35 ± 2.04, 0.63 ± 0.59, 0.75 ± 0.59, and 38.17 ± 44.22 RU/ml, respectively. There was a highly significant difference between the mean of titer anti CCP for RA with others diseases (p <0.001). We conclude that detection of anti-CCP is very useful for the diagnosis of RA and distinguishing RA from SLE. (Med J Indones 2004; 13: 227-31)